Sensitivity Analysis of Soil Gravel Parameterization on the Formation and Development of the Plateau Vortex - Pan CHENG; Shihua LÜ; Hongyu SUN; Xingyu TAO; Huiqi YOU; Fan YANG; Xuejun CAO; Jun YAN (Gaoyuan qixiang)
There were three groups of sensitivity tests to simulate and analyze a plateau low vortex that using the regional climate model RegCM4 coupled with the gravel parameterization scheme CLM4.5， which combined with the reanalysis data of high altitude， low altitude and Soil Hydrothermal parameters from European Center ERA5 for verifying simultaneously， in order to study the influence of gravel parameterization scheme on high vortex.Then the main conclusions are as follows.In the 500 hPa high-altitude situation field， especially in the stage of the occurrence and development of the plateau vortex， the closer the gravel content is to the reality， the better the simulation effect is， which means that the simulation ability of the regional climate model RegCM4 to the precipitation of Qinghai-Xizang Plateau increases with the gravel content close to the reality.In the plateau vortex area and its northeast moving path， the simulation result of 2 m temperature ascends with the increase of gravel content and the increase of gravel content provides conditions for the formation and development of the plateau vortex.The gravel parameterization scheme significantly improves the soil thermal conductivity and soil hydraulic conductivity.During the initiation and development of the plateau vortex， the closer gravel content to the reality， the closer simulated results of soil temperature and soil volume water content will be to the reality.In the extinction stage of the plateau vortex， the high content of soil gravel reduced the temperature of shallow soil significantly， which accelerates the extinction of the plateau vortex， and the effect of gravel on soil warming decreases significantly with the deeper soil layer.In the stage of generation and development of the plateau vortex， the gravel parameterization scheme CLM4.5 improve the accuracy of simulation results of the regional climate model RegCM4 obviously； and conversely， in the stage of weakening and extinction of the plateau vortex， the effects of the gravel parameterization scheme gradually reduced on the accuracy of simulation results of the regional climate model RegCM4.